UPAYA PENINGKATAN AKUNTABILITAS DAN EDUPRENEURSHIP DESA MELALUI BADAN USAHA MILIK DESA (BUMDes) LEMBANG PARINDING - Hardiyono, Hardiyono; Tikupadang, Wendy Kala (Siddiq Institute, 2023)
This research aims to increase the accountability and education of Village-Owned Enterprises (BUMDes) in Lembang Parinding. In this research, the author used descriptive qualitative research. Analysis of the interactive model using data collection techniques in the form of interviews with informants who are considered to have the potential to provide information about the role of Village-Owned Enterprises (BUMDes) in increasing Lembang Parinding Accountability and Edupreneurship, also through observation and documentation. The conclusion from the research results states that Village- Owned Enterprises (BUMDes) are not good enough at increasing accountability and edupreneurship in helping to overcome the economic problems of the community in Lembang Parinding. Independent businesses run by BUMDes are running well.